Entrepreneurship and poverty alleviation : the importance of health and children’s education for slum entrepreneurs - Shepherd, Dean A.; Parida, Vinit; Wincent, Joakim (Sage, 2020)
Research has focused on the role of entrepreneurial action in alleviating poverty. However, there is a gap between individuals’ short-term outcomes from entrepreneurship overcoming immediate resource concerns and the large-scale impact of entrepreneurship on institutional and system change. Therefore, in this study, we explore entrepreneurs’ beliefs about how entrepreneurial action can alleviate poverty. To do so, we conducted a qualitative study of entrepreneurs of businesses located in Indian slums and identified the impact of expectations, role models, and the subjective value of their children’s education in attempts to alleviate poverty.
Keywords: bottom of the pyramid (BOP); qualitative; decision making; economic development; informal; entrepreneurship; poverty; slums; entrepreneurs; social entrepreneurship; underprivileged social position; local communities; living conditions; fi=Johtaminen ja organisaatiot|en=Management and Organization|